A Drifting and Blowing Snow Scheme in the Weather Research and Forecasting Model - Saigger, Manuel; Sauter, Tobias; Schmid, Christina; Collier, Emily; Goger, Brigitta; Kaser, Georg; Prinz, Rainer; Voordendag, Annelies; Mölg, Thomas (Journal of Advances in Modeling Earth Systems, 2024)
Wind-driven redistribution of surface snow is one of the key factors leading to heterogeneous accumulation of snow at small scales. Understanding the processes that lead to this heterogeneous accumulation is, therefore, of great importance to many glaciological and hydrological questions. High-quality information on the wind field is necessary to realistically represent drifting snow. Here, we introduce a novel, intermediate-complexity drifting and blowing snow module for the Weather Research and Forecasting (WRF) model that integrates seamlessly into the standard WRF infrastructure. The module also accounts for snow particle sublimation and considers the thermodynamic feedback on the atmospheric fields. In an idealized model environment the module was tested for physical consistency. Sensitivity experiments showed that drifting snow sublimation has on the one hand local effects on the erosion and deposition patterns and on the other hand non-local effects on the larger-scale atmosphere. The simple and computationally efficient implementation allows this module to be used for small-scale and large-scale simulations in polar and glaciated regions.
CRIS-Team Scopus Importer:2024-06-21
Keywords: glaciology; model development; snow drift; WRF

A novel framework to investigate wind-driven snow redistribution over an Alpine glacier: combination of high-resolution terrestrial laser scans and large-eddy simulations - Voordendag, Annelies; Goger, Brigitta; Prinz, Rainer; Sauter, Tobias; Mölg, Thomas; Saigger, Manuel; Kaser, Georg (Cryosphere, 2024)
Wind-driven snow redistribution affects the glacier mass balance by eroding or depositing mass from or to different parts of the glacier's surface. High-resolution observations are used to test the ability of large-eddy simulations as a tool for distributed mass balance modeling. We present a case study of observed and simulated snow redistribution over Hintereisferner glacier (Ötztal Alps, Austria) between 6 and 9 February 2021. Observations consist of three high-resolution digital elevation models (ΔxCombining double low line1m) derived from terrestrial laser scans taken shortly before, directly after, and 15h after snowfall. The scans are complemented by datasets from three on-site weather stations. After the snowfall event, we observed a snowpack decrease of 0.08m on average over the glacier. The decrease in the snow depth can be attributed to post-snowfall compaction and the wind-driven redistribution of snow. Simulations were performed with the Weather Research and Forecasting (WRF) model at ΔxCombining double low line48m with a newly implemented snow drift module. The spatial patterns of the simulated snow redistribution agree well with the observed generalized patterns. Snow redistribution contributed -0.026m to the surface elevation decrease over the glacier surface on 8 February, resulting in a mass loss of -3.9kgm-2, which is on the same order of magnitude as the observations. With the single case study we cannot yet extrapolate the impact of post-snowfall events on the seasonal glacier mass balance, but the study shows that the snow drift module in WRF is a powerful tool to improve knowledge on wind-driven snow redistribution patterns over glaciers.
CRIS-Team Scopus Importer:2024-03-15